Characterization of a new splicing variant of powdery mildew resistance gene Pm4 in synthetic hexaploid wheat YAV249 - Jin, Yuli; Gu, Tiantian; Li, Xiuquan; Liu, Hong; Han, Guohao; Shi, Zhipeng; Zhou, Yilin; Fan, Jieru; Wang, Jing; Liu, Wei; Zhao, He; An, Diaoguo (Frontiers in Plant Science, 2022)
Powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is a destructive fungal disease of wheat throughout the world. Utilization of effective powdery mildew resistance genes and cultivars is considered as the most economic, efficient, and environmental-friendly method to control this disease. Synthetic hexaploid wheat (SHW), which was developed through hybridization of diploid Aegilops and tetraploid wheat, is a valuable genetic resource for resistance to powdery mildew. SHW line YAV249 showed high levels of resistance to powdery mildew at both the seedling and adult stages. Genetic analysis indicated that the resistance was controlled by a single dominant gene, temporarily designated PmYAV. Bulked segregant analysis with wheat 660K single nucleotide polymorphism (SNP) array scanning and marker analysis showed that PmYAV was located on chromosome 2AL and flanked by markers Xgdm93 and Xwgrc763, respectively, with genetic distances of 0.8 cM and 1.2 cM corresponding to a physic interval of 1.89 Mb on the Chinese Spring reference genome sequence v1.0. Sequence alignment analysis demonstrated that the sequence of PmYAV was consistent with that of Pm4a but generated an extra splicing event. When inoculated with different Bgt isolates, PmYAV showed a significantly different spectrum from Pm4a, hence it might be a new resistant resource for improvement of powdery mildew resistance. The flanked markers GDM93 and WGRC763, and the co-segregated markers BCD1231 and JS717/JS718 were confirmed to be easily performed in marker-assisted selection (MAS) of PmYAV. Using MAS strategy, PmYAV was transferred into the commercial cultivar Kenong 199 (KN199) and a wheat line YK13 was derived at generation BC3F3 from the population of YAV249/4*KN199 due to its excellent agronomic traits and resistance to powdery mildew. In conclusion, an alternative splicing variant of Pm4 was identified in this study, which informed the regulation of Pm4 gene function.